Age-Related Cutoffs of Plasma Aldosterone/Renin Concentration for Primary Aldosteronism Screening. (16th July 2018) - Ma, Linqiang; Song, Ying; Mei, Mei; He, Wenwen; Hu, Jinbo; Cheng, Qingfeng; Tang, Ziwei; Luo, Ting; Wang, Yue; Zhen, Qianna; Wang, Zhihong; Qing, Hua; et al.
Abstract : Aim . This retrospective study is aimed at investigating whether aldosterone-renin ratio (ARR) cutoffs calculated by the plasma aldosterone concentration (PAC)/plasma renin concentration (PRC) should be set differently in patients of different ages. Methods . 521 hypertensive patients were screened for primary aldosteronism (PA) by the PAC/PRC. 174 patients diagnosed with PA and 311 patients with essential hypertension (EH) were included in the final analysis. Subjects were subdivided into four age groups: <40, 40–49, 50–59, and ≥60 years old. Results . The accuracy of the ARR varied greatly among the different age groups. An ARR of 3.7 (ng/dl)/( μ IU/ml) had a sensitivity of 100% and a specificity of 80% in patients ≥ 60 years old. With this cutoff, the sensitivities in patients < 40, 40–49, and 50–59 years old were 74%, 82%, and 87%, respectively, and the specificities were 94%, 95%, and 94%, respectively. To achieve a sensitivity higher than 90%, the ARR cutoff needed to be lowered to 2.0 (ng/dl)/( μ IU/ml) for patients 40–49 and 50–59 years old, resulting in sensitivities of 90% and 95%, respectively, and specificities of 80% and 84%, respectively. To achieve a sensitivity higher than 90%, the ARR cutoff needed to be lowered to 1.0 (ng/dl)/( μ IU/ml) for patients < 40 years old, resulting in a sensitivity of 90% and a specificity of 82%. Conclusions . An ARR of 3.7 (ng/dl)/( μ IU/ml) is optimal for patients ≥ 60 years; for patients 40–59 years, the optimal ARR cutoff is 2.0; for those younger than 40 years, an ARR of 1.0 may be more reasonable.